Navigating the New Reality: A Review of the Epidemiological, Clinical, and Microbiological Characteristics of Candida auris, with a Focus on Children - Liat Ashkenazi-Hoffnung; Chen Rosenberg Danziger (Journal of Fungi, 2023)
During the past decade, Candida auris emerged across the world, causing nosocomial outbreaks in both pediatric and adult populations, particularly in intensive care settings. We reviewed the epidemiological trends and the clinical and microbiological characteristics of C. auris infection, focusing on the pediatric population. The review is based on 22 studies, which included about 250 pediatric patients with C. auris infection, across multiple countries; neonates and premature babies were the predominant pediatric patient group affected. The most common type of infection reported was bloodstream infection, which was associated with exceptionally high mortality rates. Antifungal treatment varied widely between the patients; this signifies a serious knowledge gap that should be addressed in future research. Advances in molecular diagnostic methods for rapid and accurate identification and for detection of resistance may prove especially valuable in future outbreak situations, as well as the development of investigational antifungals. However, the new reality of a highly resistant and difficult-to-treat pathogen calls for preparedness of all aspects of patient care. This spans from laboratory readiness, to raising awareness among epidemiologists and clinicians for global collaborative efforts to improve patient care and limit the spread of C. auris.